MSME Marketing Mix Strategies For The International Market : Study Of Bawang Kita MSMEs In Nganjuk - Supriono Supriono; Sudarmiatin Sudarmiatin; Rosmiza Bidin (International Journal of Management Research and Economics, 2024)
MSMEs are businesses owned by the community, both individuals and entities, that meet the criteria for being a business. Indonesia's success in increasing the scale of the national economy cannot be separated from the role of MSME behavior. MSMEs in Nganjuk Regency have their own attraction which is supported by natural potential, namely the large number of shallot commodities. As time goes by, many people in Nganjuk Regency make a living from processing shallots, so there are many similar products from MSMEs. “Bawang Kita” MSMEs face several obstacles, namely seasonal market demand which is always changing and threats from similar MSMEs which create a competitive market situation both in the national and international markets. Along with fluctuating sales and increasingly fierce competition, “Bawang Kita” MSMEs need to pay attention to marketing mix strategies that are in line with the desires of domestic and foreign consumers. This can also help companies achieve superiority over the competition. This research discusses the effectiveness of implementing international marketing mix strategies in “Bawang Kita” MSMEs which is supported by SWOT analysis. This research uses descriptive research with a qualitative approach by collecting data through in-depth interviews with MSME Owner, Resellers, and Consumers. Results of this research that the implementation of the international marketing mix strategy in “Bawang Kita” MSMEs is effective in terms of every aspect of the marketing mix which is supported by data on sales, production and distribution as well as the ability to purchase new machines. However, in the SWOT analysis carried out by researchers, there are still weaknesses in the implementation of the marketing mix carried out by MSME “Bawang Kita”. Thus, the implementation of the marketing mix strategy in “Bawang Kita” MSMEs must be further improved